Impact of interlead distance on immediate and mid-term response to cardiac resynchronization therapy. (October 2013) - Wang, Jingfeng; Su, Yangang; Cui, Jie; Chen, Haiyan; Qin, Shengmei; Ge, Junbo
Abstract Objectives. It is currently recommended that the left ventricular (LV) lead be placed at the posterolateral or lateral wall of heart during cardiac resynchronization therapy (CRT). The aim of our study is to evaluate the influence of interlead distance on immediate and mid-term response to CRT with altered right ventricular (RV) pacing site. Design. A total of 35 consecutive patients underwent CRT for standard indications. RV pacing site was altered from RV outflow tract (RVOT) to RV apex (RVA) in the course of implantation, permitting assessment of a "poorer response" and a "better response" site based on intraprocedural aortic velocity time integral (aVTI). LV–RV interlead distances were compared between these sites during operation. We also made a comparison of the interlead distances between responders and non-responders 6 months after CRT. Results. In the process of CRT implantation, the better response site showed significantly larger interlead distance (16.5 ± 4.4 cm vs.12.4 ± 5.6 cm, p = 0.001) as well as its vertical component (9.8 ± 4.8 cm vs. 4.3 ± 2.8 mm, p = 0.001) on lateral fluoroscopy view as compared with the poorer response site. Furthermore, RVA proved more likely to be the "better response" site than RVOT (91% vs. 9%, p = 0.001). At 6-month -up, responders demonstrated larger direct interlead distance (18.1 ± 4.5 cm vs. 14.8 ± 3.5 cm, p = 0.011) and horizontal interlead distance (14.1 ± 6.6 cm vs. 8.3 ± 6.1 cm, p = 0.004) on the lateral radiograph in comparison with non-responders with great significance. Conclusions. Larger interlead distance on lateral fluoroscopy view is associated with more favorable immediate and mid-term response to CRT. Use of these findings may help to maximize the benefit derived from CRT.